STUDY OF ANTIINFLAMMATION ACTIVITY OF EXTRACTS AND FRACTIONS OF SUJI LEAVES (DRACAENA ANGUSTIFOLIA (MEDIK.) ROXB.) USING PROTEIN DENATURATION AND BLOOD MEMBRANE STABILIZATION METHODS - Natalia Nugroho, Averina
Inflammation is the body's defense system in response to a foreign substance entering the body that can cause discomfort to chronic diseases such as rheumatoid arthritis. In general, inflammation can be treated using synthetic NSAID drugs. However, prolonged consumption of NSAID drugs has side effects on the gastrointestinal tract and cardiovascular effects. This is the basis for the search for active ingredients to overcome inflammation, one of which comes from natural ingredients, such as suji leaves (Dracaena angustifolia (Medik.) Roxb.). This study aims to determine the anti-inflammatory activity of suji leaf extracts and fractions. Determination of anti-inflammatory activity was carried out by protein denaturation and blood membrane stabilization methods. In addition, it aims to characterize the compounds that are contained in the anti-inflammatory active fraction using TLCspectrophotodensitometry. Extraction was done using multistage maceration method using n-hexane, ethyl acetate, and 70% ethanol solvents. Anti-inflammatory activity was tested by protein denaturation and blood membrane stabilization methods. The extract with the best anti-inflammatory activity was shown by ethyl acetate extract with IC50 value of 64.47 ± 1.357 µg/mL in protein denaturation test and IC50 value of 2651.64 ± 33.037 µg/mL in blood membrane stabilization test. The ethyl acetate extract was then fractionated by vacuum liquid chromatography method using gradient elution of a mixture of nhexane, ethyl acetate, and ethanol solvents. Fraction with the best anti-inflammatory activity was shown by fraction 6 with IC50 value of 27.079 ± 0.233 µg/mL in protein denaturation test and IC50 value of 1910.50 ± 29.1 µg/mL in blood membrane stabilization test. Fraction 6 characterization results using TLCspectrophotodensitometry showed the presence of compounds that have Rf values and spectrum shapes identical to apigenin compounds. Therefore, it can be concluded that the best anti-inflammatory activity is shown by ethyl acetate extract and fraction 6 of suji leaves based on protein denaturation method and blood membrane stabilization method. TLC-Spectrophotodensitrometry analysis results showed that fraction 6 contained apigenin compounds. Further characterization and identification are needed in the development of anti-inflammatory preparations based on active fractions of suji leaf plants.